The evaluation criteria used in the decision making process of funds investment in capital entrepreneur - Marques, Vagner Antônio; Souza, Antônio Artur de; Costa Junior, Atair Ferreira da (Revista de Administração da UFSM, 2015)
This study aimed to verify the criteria used by the funds Venture Capital / Private Equity in investment decisions. For such, held a multicase study at three managers of investment funds. Data collection was conducted through questionnaires and interviews (structured and semi-structured) from September 2010 to December 2010. It was observed that the managers of the cases studied using the following criteria as having the greatest impact on the evaluation process: the management team and their skills, product-market fund and criteria, these criteria mentioned by Muzyka et al. (1996). About this result, one must note two aspects: (i) the preoccupation with the management capacity is considered by managers as the most relevant criterion for maximizing the chances of projects being implemented, and (ii) the criteria of the fund, unlike that found in Pottery search et al. (1996), there are subsidiary, which probably stems from the expertise and / or regionalization of the investment portfolio, as well as aspects of Brazilian regulations that establish limits for target companies.